Erythema Annulare Centrifugum as a Manifestation of Secondary Syphilis [Eritema Anular Centrífugo Como Manifestación de Sífilis Secundaria] - Fuenzalida-Cruz, H; Chavez-Rojas, F; Cardemil-Balari, A; Soto-Madrid, D (Ediciones Doyma, S.L., 2018)
[No abstract available]